Caring behavior and its impact on patient safety activities: Investigating the role of safety competency - Lusianah, Lusianah; Muliyadi, Mulyadi; Kurniawati, Any; Asmirajanti, Mira (Jurnal Keperawatan Padjadjaran, 2025)
Background: Patient safety is a critical component of healthcare. Caring behavior among nurses is hypothesized to enhance patient safety activities. However, the relationship between caring behavior and patient safety activities, particularly the moderating role of patient safety competency, remains underexplored. Purpose: This study aims to examine the influence of caring behavior on patient safety activities, while assessing the moderating role of patient safety competency. Methods: This study employed Structural Equation Modeling (SEM) to analyze the relationship between caring behavior and patient safety activities. A total of 154 nurses from a private hospital in Tangerang participated. The caring behavior inventory (CBI) was used to assess the nurses' caring behaviors across four subscales: respectful communication, ensuring human presence, communication with a positive disposition, and professional knowledge and skills. The safety nursing activities scale evaluated comprehensive patient safety activities across eight subcategories, such as communication, operations, and risk management. The Patient Safety in Nursing Education Questionnaire (PaSNEQ) was employed to assess patient safety competency, comprising three subdomains: basic patient safety competency, clinical analysis and action effectiveness, and error prevention strategies and additional training.   Results: The analysis showed that caring behaviour significantly influenced patient safety activities (T-value = 7.70, p < 0.05). Patient safety competency did not significantly moderate this relationship (T-value = 1.21). Conclusions: Caring behavior significantly improves patient safety, although increased patient safety competency does not show significant moderation effects. Future research should explore alternative moderators and emphasize interventions that foster caring behaviour to strengthen patient safety outcomes.